EVALUATION TECHNIQUES FOR ASSESSING VOCATIONAL AND TECHNICAL EDUCATION PROGRAMMES - Ibrahim, Dalhatu Isa (Sokoto Educational Review, 2020)
This paper attempts to present a wide range of evaluation techniques useful in assessing vocational and technical education programmes. The techniques outlined in this write up are not exhaustive due to space and time constraint. However, the most important areas were given detailed treatment. Functions of evaluation in vocational and technical education which give rise to the three (3) main types of evaluation namely; formative, summative and ultimate were explained. Finally, the meaning and approaches to programme evaluation in line with technical and vocational education programme were also highlighted.